Changing Notes in the Voices beyond the Rooster Coop: A Neo-Capitalist Coup in Aravind Adiga’s The White Tiger - Shetty, Praveen; Prabhu, Vishnumoorthy; T., Pratapchandra (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Aravind Adiga’s novel The White Tiger encapsulates the complexities of identity formation in a milieu effected by neo-capitalism. The novel, for many, is about a new identity made available to the hitherto marginalized in the form of opportunities unveiled by market forces. It is also perceived as a registration of the frustration and anger of the deprived that has become conscious of the new possibilities. Understandably, interpreting the novel on these lines leads to the identification of the protagonist Balram as a champion of the marginalized, settling scores with the oppressive systemHowever, there are far subtler notes in the protagonist’s attitude to these sweeping changes than the simple and one dimensional approach of an achiever who is able to break the “rooster coop” and revel at the reversal of fortune. Neither is it a representative voice of the suppressed class turning the table on its oppressor by using the opportunities offered by the global market. The “notes” of the voices that emerge as Balram, the boy from darkness, moves up the ladder to become Ashok Sharma, the entrepreneur hiding in light, not only lack symphony but also create a distinct dissonance. Clearly, the discord in the changing notes is brought about by the forces that changed the world he lives in—a neo-capitalist world. The whole process of Balram turning into Ashok Sharma is a neocapitalist coup.